A study to assess the knowledge on computer aided learning programs among students attending Kenya Medical Training College, Nairobi campus - Omambia, Salim M.; Kivungi, Mutiso N. (Advances in Social Sciences Research Journal, 2018)
Computer Assisted Learning (CAL) is a method of acquiring knowledge using electronic media which is gaining recognition among students. This requires access to computers and considerable awareness on information technology. Studies the world over have also highlighted the roles of computer as an instructional material in the classroom particularly in regard to assisting in enriching the teaching learning. Objective: The objective of this study sought to assess the knowledge on computer aided learning programs among students attending Kenya Medical Training College, Nairobi campus Methods: This study was a descriptive research study, the targeted population of the study were 4,490 KMTC Nairobi Campus students, and the sample technique used was random sampling. Data was collected from respondents by use of a questionnaire, and the analysis was based on the findings obtained from the questionnaire. Data presentation was in form of descriptive statistics such as frequency distribution, percentages, pie charts, bar graphs and tables. Results and Discussions: The data from the knowledge on computer aided learning programs were summarized in three main evaluation areas targeting the ICT access, student perception and frequency of computer use. From the findings, there was a significant association between knowledge and perception of ICT and participants sex (p = 0.001). Females were more likely to have positive responses compared to males (72.3 versus 49.9%). Access point was also associated with perception (p = 0.005). Accessing computers in the computer lab was associated with higher Likert scale responses. The perception of CAL among the students was closely associated with how much the students access the CAL and their knowledge on computers at KMTC. 184 (97.4%) of the participants reported that computers were available in college, and 138 (74.6%) said that the access point were the computer laboratory. These findings were in line with the Kenyan Government agenda for increasingly acquiring computers to equip all the public schools and institution of higher learning according to the Ministry of Education Science and Technology Sessional Paper, (2012). Conclusions: Based on the results and discussions, among the main problems that key informants described during the study, regardless of the fact that there was a significant association between knowledge and perception of ICT and participants gender, female students had more access to CAL facilities as compared to the male students. Hence the female students at KMTC had more knowledge as compared to the male students with regards to CAL Recommendations: KMTC in collaboration with the MOE needs to come up with a standardised guideline for CAL implementation